Descemet’s membrane area and posterior corneal power may predict the Descemet membrane folds after deep anterior lamellar keratoplasty in patients with advanced keratoconus - Ozgur, Armagan; Ucgul, Ahmet Yucel; Cubuk, Mehmet Ozgur; Onat, Emrah; Ceylanoglu, Kübra Serbest; Aydın, Bahri; Yuksel, Erdem (Springer Science and Business Media LLC, 2021)
To investigate possible predictive topographic characteristics for the development of Descemet's membrane (DM) folds after the uneventful deep anterior lamellar keratoplasty (DALK).A retrospective study included 56 eyes of 56 consecutive patients who underwent uneventful DALK using the big-bubble technique to treat advanced keratoconus. At baseline and each visit, best-corrected logMAR visual acuity (BCVA), slit-lamp findings, endothelial cell density, topographic parameters were recorded. DM area is calculated using morphogeometric modelling.Twelve (21.4%) of them exhibited DM folds, whereas the remaining 44 (78.6%) did not exhibit any DM folds after the surgery. The mean follow-up time was 36.3 ± 16.7 (range, 12-71) months. The mean posterior corneal power was - 13.8 ± 0.6 D in patients with DM folds, whereas - 13.0 ± 0.8 D in those without DM folds (p = 0.016). The mean DM area was 53.6 ± 2.3 (50.9-57.9) mm2 in patients with DM folds, whereas 51.6 ± 1.7 (47.1-53.9) mm2 in those without DM folds (p = 0.001). The ROC curve showed that two best cut-off value for the posterior corneal power and DM area were 13.75 D and 53.8 mm2, respectively, to predict the occurrence of DM folds.DALK surgery seems to cause DM folds in patients with large DM area and high posterior corneal power.
Keywords: Visual Acuity; Keratoconus; Descemet's Membrane Area; Cornea; Corneal Transplantation; Deep Anterior Lamellar Keratoplasty; DALK; Posterior Corneal Power; Advanced Keratoconus; Humans; Descemet's Membrane Folds; Descemet Membrane; Retrospective Studies